The Influence of Removing the Perception of Achievement on Performance in Volitional Time-to-Exhaustion Cycle Ergometer Trials - Ross Lorimer; John Babraj (International Universities Strength and Conditioning Association, 2020)
The purpose of this brief report is to report the findings of an investigation of the potential influence of the removal of achievement feedback on subjects undertaking maximal fitness testing. Subjects were asked to complete a two incremental volitional time-to-exhaustion cycle ergometer trials, one with feedback and one without. The final minute of each trial, following the last increase in increment in resistance was broken down into four 15-second intervals and a frequency count made of how many subjects stopped within each interval. A chi-square test was used to determine that there was a significant difference between the expected frequencies and the observed frequencies (p<0.05) in the feedback condition. With feedback, subjects were significantly more likely to stop in the first interval (0-15s) while without feedback subjects were evenly distributed across all four intervals. There was also a non-significant, but medium-to-large difference, in time-to-exhaustion with those in the feedback condition going an average 39.44s longer. This suggests a potential psychological element related to goal achievement that influences performance in incremental volitional time-to-exhaustion cycle ergometer trials. The information subjects have available on which to base goals (level of increment, time etc.) needs to be managed to prevent spontaneous goal setting and ensure true time-to-exhaustion is achieved.